Application of endoscopic ultrasound‐guided‐fine needle aspiration combined with cyst fluid analysis for the diagnosis of mediastinal cystic lesions. Issue 2 (27th November 2018) - Zhao, Yuchong; Wang, Ronghua; Wang, Yun; Chen, Qian; Chen, Liangkai; Hou, Wei; Liu, Limin; Gao, Wei; Cheng, Bin
Abstract : Background: Mediastinal cystic lesions account for approximately 15–20% of all mediastinal masses and are difficult to differentiate because of similar imaging manifestation. The aim of this study was to differentiate mediastinum cystic lesions through endoscopic ultrasound‐guided‐fine needle aspiration (EUS‐FNA) and parameters from cyst‐fluid analysis. Methods: Over a period of eight years, 37 patients suspected with mediastinal cystic lesions were assessed. Cyst fluid was collected via EUS‐FNA and further examined using cytological and biochemical techniques. Definitive diagnosis was established based on cytology, surgical pathology, and/or clinical follow‐up. Results: Based on the final pathological reports or long‐term follow‐up, 19 patients were diagnosed with benign cysts, 14 with benign or malignant tumors, 2 with tuberculosis, 1 with an abscess, and 1 with a pancreatic pseudocyst. Computed tomography or magnetic resonance imaging mistakenly distinguished eight cases as solid masses (27.03%), but EUS revealed cystic characteristics. Carcinoembryonic antigen and lactate dehydrogenase (LDH) were evaluated from the cyst fluid obtained by EUS‐FNA. There was no statistically significant difference in carcinoembryonic antigen values between benign and malignant cysts; however the average LDH value in the malignancy group was significantly higher than in the benign group. Conclusion: EUS‐FNA showed great potential for differentiating mediastinal lesions by combining imaging manifestation and cytological examination. The elevated LDH value from cyst fluid chemical analysis could be used as an auxiliary indicator for diagnosing malignancy.